Learning robotics using Python : design, simulate, program, and prototype an autonomous mobile robot using ROS, OpenCV, PCL, and Python - Joseph, Lentin (Packt Publishing, 2018)
"Learning about robotics will become an essential skill as it will be a ubiquitous part of life. Even though robotics is a complex subject, several other tools along with Python can help you design a project to create an easy-to-use interface. The main aim of the book is to teach you how to build an autonomous mobile robot from scratch -- provided by publisher